Long-term efficiency of infliximab in patients with ankylosing spondylitis: real life data confirm the potential for dose reduction. Issue 2 (19th July 2016) - Baraliakos, X; Heldmann, F; van den Bosch, F; Burmester, G; Gaston, H; van der Horst-Bruinsma, I E; Krause, A; Schmidt, R; Schneider, M; Sieper, J; Andermann, B; van Tubergen, A; et al.
Abstract : Objective: To analyse the treatment outcome of patients with ankylosing spondylitis (AS) in the European AS infliximab cohort (EASIC) study after a total period of 8 years with specific focus on dosage and the duration of intervals between infliximab infusions. Methods: EASIC included patients with AS who had received infliximab for 2 years as part of the ASSERT trial. After that period, rheumatologists were free to change the dose or the intervals of infliximab. Clinical data were status at baseline, end of ASSERT and for a total of 8 years of follow-up. Results: Of the initially 71 patients with AS from EASIC, 55 patients (77.5%) had completed the 8th year of anti-tumour necrosis factor (TNF) treatment. Of those, 48 patients (87.3%) still continued on infliximab. The mean infusion interval increased slightly from 6 to 7.1±1.5 weeks, while 45.8% patients had increased the intervals up to a maximum of 12 weeks. The mean infliximab dose remained stable over time, with a minimum of 3.1 mg/kg and a maximum of 6.4 mg/kg. In patients receiving <5 mg/kg infliximab, the mean infusion interval increased to 7.0±1.2 weeks. In total, the mean cumulative dose per patient and per year decreased from 3566.30 to 2973.60 mg. Conclusions: We could observe that over a follow-up of 8 years of treatment with infliximab, >85% patients still remained on the same treatment, without any major safety events. Furthermore, both the infusion intervals and also the mean infliximab dose were modestly reduced in ≥70% of the patients without the loss of clinical efficiency.